Asupan Energi, Asupan Protein, Penyakit Infeksi dan Pengetahuan Ibu Mempengaruhi Status Gizi Buruk di Wilayah Puskesmas Dempet Kabupaten Demak - Khoiriyatun, Khoiriyatun; Supadi, J; Rahayuni, Arintina (Poltekkes Kemenkes Semarang, 2014)
Background : The problem of malnutrition is influenced by many factors. They are direct factors and indirect factors. Direct factors are the imbalance of food and infected diseases that the children under five years old suffer from. Energy intake is on the average of 73,6% from AKG, protein intake is on the average of 83,5% from AKG. Low education background (graduated from elementary school 41,6%) influences the lack of knowledge of parents about nutrition and health, especially mothers. This is also one of the factors of malnutrition of children under five years old. Prevalence of malnutrition in Dempet is 1,4%.Objective : To know the factors that influence malnutrition status of children under five years old in the working area of public health centre Dempet, Dempet district, Demak regency.Method : Analytic research with case control frame with retrospective approach. Case sample consists of 49 and control sample is also 49. Date are computed and analyzed by using Chi-Square test and Odds ratio test to know how big malnutrition factors are.Results : Energy intake is less found in case group (87,8%), good energy intake is found in control group (89,8%). Protein intake is less found in case group (71,45%), good protein intake is found in control group (95,9%). Suffering from infection diseases is found in case group (87,8%), not suffering from infection diseases is found in control group (77,6%). Having lack of knowledge is found in case group (71,4%). Having good knowledge is found in control group (59,2%). There is asignificant influence between energy intake with value of p=0,000, odds ratio is 63,037, protein intake with value of p=0,000, odds ratio is 58,750, infection event with value of p=0,000, odds ratio is 24,758 and knowledge with value of p=0,002, odds ratio is 3,625 with malnutrition status of children under five years old.Conclution : Energy intake, protein intake,infection diseases and mothers knowledge influence malnutrition status in the working area of public health centre Dempet, Demak.